2002
DOI: 10.1124/jpet.102.038380
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human T Cell Activation by Novel Src Kinase Inhibitors Is Dependent upon the Complexity of the Signal Delivered to the Cell

Abstract: The activity of a novel series of protein tyrosine kinase inhibitors that are selective for the Src family has been assessed. The activity of these compounds [named CT-SKI (Celltech Src kinase inhibitors)] was investigated by assessing their potential to modulate T cell receptor activation, an event thought to involve the Src kinases Lck and Fyn. This series of compounds contained low-nanomolar inhibitors of Src kinases with selectivity over Csk, epidermal growth factor receptor kinase, protein kinase C, and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…When the responses to these SAgs were tested, we observed that the Y205A SEE failed to induce IL-2 production by Lck-deficient T cells, whereas both the wildtype SEE and the K148A SEE induced substantial IL-2 production by these cells ( Figure 2G). Together, these results confirm with multiple approaches that the response of human primary T cells and T cell lines to SEE and other SAgs does not require the canonical Lck-dependent signaling pathway (Criado and Madrenas, 2004;Rapecki and Allen, 2002;Yamasaki et al, 1997).…”
Section: Lck Is Not Required For Activation Of Peripheral Blood T Celsupporting
confidence: 80%
See 1 more Smart Citation
“…When the responses to these SAgs were tested, we observed that the Y205A SEE failed to induce IL-2 production by Lck-deficient T cells, whereas both the wildtype SEE and the K148A SEE induced substantial IL-2 production by these cells ( Figure 2G). Together, these results confirm with multiple approaches that the response of human primary T cells and T cell lines to SEE and other SAgs does not require the canonical Lck-dependent signaling pathway (Criado and Madrenas, 2004;Rapecki and Allen, 2002;Yamasaki et al, 1997).…”
Section: Lck Is Not Required For Activation Of Peripheral Blood T Celsupporting
confidence: 80%
“…In addition to the cellular data, biochemical experiments indicate that bacterial SAg such as Staphylococcal enterotoxin E (SEE) can activate Lck-deficient, CD4 2 or lo T cells (Criado and Madrenas, 2004;Rapecki and Allen, 2002;Yamasaki et al, 1997). In fact, Lck is not only dispensable but, as we and others have recently shown, it can also downregulate SAg-induced T cell activation by turning on a negative regulatory feedback on TCR signaling (Criado and Madrenas, 2004;Methi et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…However, our observation that PP2 enhances the response of some primary T cell subsets to SEE argues that not only is Lck dispensable in this response, but it may play a negative regulatory role. This possibility is suggested by recent observations of the apparent lack of inhibition of T cell responses using novel Src kinase inhibitors (33). To avoid problems in experimental interpretation that could arise from the polyclonal nature of primary T cells and the variability in the levels of expression of Src kinases in these cells, we took advantage of the availability of Jurkat T cells and their Lck-deficient and Lck-reconstituted counterpart lines to address the question of whether Lck is involved in signaling to negative regulatory pathways.…”
Section: Resultsmentioning
confidence: 93%
“…PP2 is at least 1,000-fold more active against Src family kinases than other TCR-associated tyrosine kinases [26, 27]. It has also been shown that PP2 is effective in blocking the anti-CD3-induced T-cell activation events, while it is less effective at inhibiting the TCR-independent proliferation induced by phorbol ester and IL-2 [28]. To determine directly whether IL-2R signaling is necessary for CD25 expression in intact T-lymphocytes, we used WHI-P131 (4-(4´-Hydroxyphenyl)amino-6,7-dimethoxyquinozoline) as an effective inhibitor of IL-2R-associated tyrosine kinase JAK3.…”
Section: Resultsmentioning
confidence: 99%